Hubungan Kenaikan Berat Badan Ibu Hamil Trimester III terhadap Penambahan Berat Janin Menjelang Persalinan di SMC RS Telogorejo - Novia Nurkumalasari; Tia Nurhanifah; Qomariyah Qomariyah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
One measure of neonatal health is birth weight. Both the mother's weight increase and her overall health during the pregnancy have an impact on the baby's birth weight. This study sought to ascertain how pregnant women's weight gain related to the interpretation of fetal weight prior to delivery at Telogorejo Semarang Hospital. Research Design: Correlation design using quantitative research methodology. All of the pregnant patients that underwent ANC at Telogorejo Hospital in April 2024 made up the study's population. Purposive sampling was the method employed in the sampling process. acquired a 52-person sample. instruments for gathering data from medical records. Chi square testing is the method employed. Findings: Pregnant women's weight gain and fetal weight gain prior to birth have a substantial correlation (p = 0.000). As many as 24 respondents (46.2%) reported a normal weight gain of 9–12 kg, and as many as 22 respondents (42.3%) reported a fetal weight of more than 2.9 kg. Conclusion: At SMC Telogorejo Hospital, there is a noteworthy correlation between pregnant women's weight rise and the weight gain of the fetus prior to birth. Recommendation: The hospital should prepare a strategy for early identification of changes in weight gain during pregnancy that could affect the developing fetus and for counseling.